Ambiguity and Conflict in Practice: A Conceptual Model for the Equitable Implementation of Title IX. Issue 4 (2nd October 2022) - Harry, Molly; Graves, Ellen I.; Hall, Alex
Abstract : Title IX is often viewed as vague and contentious, causing scholars and practitioners much grief in understanding and enforcing the legislation, particularly regarding the rights and experiences of trans students. This manuscript offers a new conceptual framework to assist scholars and practitioners in recognizing how two factors, ambiguity and conflict, influence implementation of Title IX. Specifically, this manuscript proposes the Ambiguity-Conflict Continua Model to examine the impact of Title IX's ambiguity and conflict in two court cases related to trans students' experiences. From application of this model, specific recommendations emerge, including: (1) improving understanding of Title IX, associated documents, and institutional policies; (2) attending to specific regulatory changes and court cases related to Title IX; (3) centering students' experiences at their institutions; and (4) developing and implementing enhanced policies for equity, particularly for trans students.